MEMBENTUK KEDIPLINAN DAN MOTIVASI BELAJAR MAHASISWA: STUDI BERDASARKAN PEMIKIRAN JOHN DEWEY - JUNTAK, JUSTIN NIAGA SIMAN; SETYANTI, ELIANA; ANAKOTTA, ELKA; LESILOLO, HERLY J. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Education is something that is planned and planned from an educational person to his students, so that the goals of education can be achieved. Likewise, the education carried out at UKTS as a private campus in Surakarta includes lectures in the SPARK program which carries the concept of Smart, Proactive, Innovative, Collaborative, Christian Values which is expected to bring progress in the field of education. One way to realize student discipline and motivation to learn is to hold morning and afternoon assembly activities with a semi-military